Examining a display-peeping prevention method that uses real-time UI part transparency linked to motion detection by video analysis - Koki Kishibata; Masaki Narita (Institute of Advanced Engineering and Science, 2021)
In recent years, the use of various information terminals such as smartphones and personal computers have become widespread, and situations where information terminals are used have become diverse. With increased opportunities to use information terminals outdoors and during travel, some users have been using peep-prevention filters, or software with an equivalent function, on their displays, in order to protect their privacy. However, such filters have problems with regards their effectiveness, ease of use, and the user being able recognize when they are vulnerable to peeping. Decrease in display visibility, unprotected angles, and the fact that it is difficult for users to notice when others are watching their screen, are some examples of such problems. Also, recently, many information terminals recently distributed have built-in cameras. In this paper, in order to solve the aforementioned problems, we propose to detect motion, video analyze , and transparentize part of the user interface (UI) in real time by using a laptop’s built-in camera. This method is enabled with low-load and can be applied to various terminals. Further, in order to verify the effectiveness of the method, we implemented a prototype, and carried out an evaluation experiment on experimental subjects. Results from the experiment confirmed that real-time UI transparentization is a very effective method for protecting privacy of information terminals.